ORNAMENTATIONS OF PERFORMANCE OF CERTAIN MUSICAL INSTRUMENTS - Muminova Dilfuzakhon Numonovna (Journals Park Publishing, 2022)
In this article, we will talk about the development of the playing skills of the melody, the development of the Clavier art, difficult strings, Singaporean, mordent, Triol, melism, Trell.
Keywords: keyboard; art; barcode